Citofilogenia do clado ACPT (Subordem Cactineae, Caryophyllales) e caracterização citogenética de espécies dos gêneros Portulaca L. e Talinum Doweld - MARINHO, Maria Angélica Oliveira (2018)
Molecular phylogenetic evidence, as well as comparative morphological investigations, allowed us to propose a revised family classification of the suborder Cactineae, recognizing eight monophyletic families. However, they indicate controversial hypotheses between the families of the ACPT clade (Anacampserotaceae, Cactaceae, Portulacaceae and Talinaceae). For each family there appears to be a distinct basic chromosome number, which has not yet been tested from an evolutionary and phylogenetic point of view. In order to contribute to the cytogenetic characterization in the group and to help understand the evolution of the chromosome numbers, a cytophilogenesis (a study of molecular phylogeny combined with cytogenetic data) was carried out based on chromosome numbers. A citomolecular analysis of Portulaca and Talinum species based on chromosomal characteristics, such as banding and distribution of rDNA sites 5S and 35S was also performed. The analysis of character reconstruction of ancestral haploid numbers suggested n = 12 for Cactineae, with different basic numbers for each family of the clade ACPT: Cactaceae and Montiaceae (n = 11), Talinaceae (n = 12) and Anacampserotaceae and Portulacaceae (n = 9). The chromosome evolution of this suborder was mainly due to events of descending disploidia and polyploidy, and the low phylogenetic resolution among the families of the ACPT clade was due to a family divergence within a short period of time. The species of Portulaca and Talinum studied cariologically presented symmetrical karyotypes and small chromosomes, with chromosomal numbers varying from 2n = 18 to 54 in Portulaca and from 2n = 24 to 72 in Talinum, with basic chromosome numbers x = 9 and x = 12, respectively. A pair of satellites close to the centromere were observed in most Portulaca species and in the terminal region in the Talinum and P. oleracea silvestre species, in all cases co-located with the rDNA regions 35S. It was observed the presence of heteromorphism in a chromosomal pair in P. grandiflora. In addition, CMA+/DAPI- proximal bands were observed on the chromosomes of T. paniculatum, P. grandiflora and P. hirsutissima. The results confirmed the existence of cyto-molecular variation among the subspecies of Portulaca oleracea, which may be useful for their differentiation. The karyotype variety within Portulacaceae and Talinaceae added to the cyto-molecular analyzes of Cactaceae representatives suggest an extensive plasticity in the repetitive fraction of the genomes of the suborder Cactineae.